2020
DOI: 10.1111/bjd.19675
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and appraising patient‐reported outcome measures on treatment satisfaction in acne: a systematic review*

Abstract: Background After dermatitis, acne is the next skin disease to contribute most to the burden of skin diseases worldwide. Recently, seven core outcome domains have been identified, which together form an Acne Core Outcome Set (ACORN). One of these was satisfaction with acne treatment. Objectives To identify studies that described the development of patient-reported outcome measures (PROMS), evaluated one or more measurement properties of a PROM, or evaluated the interpretability of a PROM in patients with acne r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 222 publications
1
8
0
Order By: Relevance
“… Although substantial progress has been made in developing and publishing core outcome domains for many dermatological diseases, 1 there is still a long way to go. The findings from van Zuuren et al 5 . are comparable to many other areas where many different OMIs are used for similar outcome domains with insufficient or unknown measurement properties 6–8 .…”
supporting
confidence: 70%
See 1 more Smart Citation
“… Although substantial progress has been made in developing and publishing core outcome domains for many dermatological diseases, 1 there is still a long way to go. The findings from van Zuuren et al 5 . are comparable to many other areas where many different OMIs are used for similar outcome domains with insufficient or unknown measurement properties 6–8 .…”
supporting
confidence: 70%
“…Having identified core domains is critical, but is only one step towards a complete COS. In addition to efforts to select and to define core outcome domains according to the highest methodological standards, the same attention must be paid to identify and to develop OMIs. The joint COSMIN and COMET guidance on how to best select OMIs per core domain 3 should be followed as van Zuuren et al 5 . did.…”
mentioning
confidence: 99%
“…Built upon the principles of collaborative working, these groups may prove transformative for research as systematic reviews frequently identify a lack of consistency around outcome sets. Through consensus, the Acne Core Outcomes Research Network (ACORN) [ 29 ] identified core domains for measurement within the context of a clinical study and noted discrepancies between patients and clinicians regarding the impact of acne [ 30 , 31 ]. ACORN is now developing novel tools where no validated measurements are currently available.…”
Section: Ppi As Applied To the Dermatology Research Processmentioning
confidence: 99%
“…Only one study described development of an acne treatment satisfaction measure, but development was inadequate and lacking in measurement properties. The conclusion was that there is an unmet need in measurement development for treatment satisfaction in acne [24].…”
Section: Reportmentioning
confidence: 99%